Laparoscopic Approach to Large Bowel Neoplastic Obstruction After Self-Expandable-Metal-Stent (SEMS) Placement. Issue 2 (April 2019) - Berselli, Mattia; Borroni, Giacomo; Livraghi, Lorenzo; Quintodei, Valeria; Sambucci, Daniele; Cortelezzi, Claudio; Segato, Sergio; Carcano, Giulio; Cocozza, Eugenio
Abstract : Endoscopic self-expandable metal stent (SEMS) placement as a bridge to surgery in large bowel neoplastic obstruction is an alternative to emergency surgery for the obstructive colorectal neoplasms. This study aims to analyze postoperative and long-term outcomes in a series of patients who underwent laparoscopic colorectal resection after SEMS placement. The analysis, after the stratification based on the time elapsed between the onset of the occlusive symptoms and the SEMS positioning, revealed an interesting result, with lower mortality for patients who underwent the procedure within 24 hours of hospitalization ( P =0.0159). This trend may indicate the need to reduce the endoscopic time schedules as much as possible, even if an emergency procedure is needed. The laparoscopic approach, after stent placement as bridge therapy, can be a safe alternative to emergency surgery, if the procedure is precociously applied.